How To Set Up An Information Platform For Migrants Lessons learned from a transnational multilingual tool Danube Compass - Bofulin, Martina (ZRC SAZU, Založba ZRC, 2018)
Transnational multilingual information platform Danube Compass, part of the DRIM project (Danube Region Information Platform for Economic Integration of Migrants) financed by the European Union's Danube Transnational Programme, was created with the aim to improve access to information for migrants in eight countries along the Danube river. What we have learned in the process is what this handbook is all about. Its aim is to support the creation of similar platforms in other regions and is intended for organizations and institutions involved in the integration of newly arrived migrants. It should be helpful for anyone who is thinking of gathering focused information about arriving, working and living in another country. It provides hands-on checklists and ideas about how to implement one's own platform for supporting migrants' integration on local or national level.